The impact of racist joke on black people’s self - Ribeiro, Thaís Diniz; Santos, Raissa Cruz dos; Borba, Aécio (Perspectivas em Análise do Comportamento, 2023)
Behavior Analysis has shown interest in social issues in order to intervene in problems such as racism. This essay proposes a theoretical reflection on the effects of racism on the construction of the self of black people, with a focus on microaggressions, especially the racist joke. To do so, we present how racial microaggressions can be understood based on the notion of relational frames, and their impact on the learning of symbolic relationships. Then, we depart from these theoretical elaborations to discuss the functions of racist jokes and their consequences for the construction of the self of black people. We conclude that racist jokes, as part of learned relationships, interfere in the formation of the self to the black people as something inferior and worthy of contempt in several aspects.